A modeling assessment of the origin of Beryllium‐7 and Ozone in the Canadian Rocky Mountains. Issue 17 (13th September 2013) - D'Amours, R.; Mintz, R.; Mooney, C.; Wiens, B. J.
Abstract : [1] This paper seeks to investigate the extent to which stratosphere‒to‒troposphere transport (STT) impacts the Canadian Rocky Mountain foothills. Beryllium‒7 ( 7 Be) was monitored weekly at Harlech, Alberta, from July 2003 to June 2004, and daily during the spring of 2004. These data, together with hourly ozone (O3 ) and relative humidity (RH) measurements, are presented and analyzed, with a focus on the spring of 2004. A Lagrangian dispersion model was used to help determine the origin of air parcels arriving at Harlech in order to assess if these periods were related to well‒defined stratospheric intrusions. The modeling results show that events consisting of above average surface observations of 7 Be and O3, and below average surface observations of RH, are the result of the arrival of air originating from the middle and upper troposphere. During the spring of 2004, no direct STTs were observed; all identified events were determined to be indirect STTs or middle to upper troposphere transport that occurred several days prior to being detected at Harlech. The most significant event occurred between 2 and 11 April, which had the longest period of elevated 7 Be and O3 observations and the lowest RH measured during the spring of 2004, and where the modeling showed a strong stratospheric input. This input can be connected with two well‒defined stratospheric intrusions occurring over the northern Pacific Ocean, more than 5 days before the associated surface observations. Furthermore, the modeling shows that periods of below average 7 Be and O3 occurred when the station was mainly influenced by air masses circulating in the boundary layer. Key Points: 14‐day inverse modeling for daily 7Be and O3 in Alberta, March‐June 2004 Only indirect stratospheric intrusions can be associated to high concentrations Low concentrations are associated mainly to boundary layer air masses